THE ABILITY TO READ RESEARCH ARTICLES: PROFILE OF STUDENTS IN THE BIOLOGY EDUCATION PROGRAMS' OF UIN WALISONGO SEMARANG - Wijayanti, Erna; Adi, Widi Cahya (Universitas Tanjungpura, 2022)
This study aims to determine the profile of students of the undergraduate Biology Education program at UIN Walisongo Semarang. This study is descriptive qualitative with a survey method. The number of participants was 96 students of the Biology Education Program from different years. The instruments used were reading scientific articles and tests of the ability to read scientific articles. Data in the form of test answers, given a score and analyzed using the formula mean and percentage, then categorized. The results showed that the student's ability to read research articles was categorized as very low (Counterargument (15.67%) and Refutation (1.8%)), low (Motive (35.62%), Support (23.85), and Implication (28.17)), moderate (Novelty, 52.92%), and high (Objective (75.59%) and Main Conclusion 76.55%)). This research concludes that the ability to read scientific articles of undergraduate biology education students still needs improvement by applying learning methods/models or giving an assignment that can improve the ability to read scientific articles.